Hyperfine interactions in and lattice parameters of pyrochlore and defect fluorite (Eu1−xNdx)2Zr2O7. (April 2015) - Klobes, B.; Finkeldei, S.; Röhrig, W.; Bosbach, D.; Hermann, R.P.
Abstract: Pyrochlore and defect fluorite ( Eu 1 − x Nd x ) 2 Zr 2 O 7 compounds ( x =0, 0.5 and 0.75) synthesized by a wet chemical approach were investigated using temperature dependent high energy X-ray diffraction as well as 151 Eu Mössbauer spectroscopy. Diffraction data reveals an increase in lattice parameter with increasing Nd content, an increase that is disproportionally large between x =0.5 and 0.75. The 151 Eu Mössbauer spectral parameters, i.e. isomer shift and quadrupole splitting, fall in separate regions for pyrochlore and defect fluorite type compounds. Between 80 and 350 K, the impact of the order–disorder, i.e. pyrochlore to defect fluorite, transition on isomer shift and quadrupole splitting is found to exceed the one due to lattice expansion. Abstract : Highlights: Eu 151 Mössbauer parameters in defect fluorite and pyrochlore ( Eu 1 − x Nd x ) 2 Zr 2 O 7 . Thermal expansion in ( Eu 1 − x Nd x ) 2 Zr 2 O 7 by high-energy XRD. Lattice parameters do not follow Vegard's law with Nd content. Defect fluorite and pyrochlore compounds distinguishable using isomer shifts.